A Review of Non-Marine Sequence Stratigraphy - F. Hasan Sidi (Berita Sedimentologi, 1997)
There has been a virtual explosion of stratigraphic studies utilizing the principles of sequence stratigraphy recently. Although the concept of time stratigraphy is not new, the packaging of depositional units into system tracks and sequences is. Sequence stratigraphy has evolved from the original concepts of seismic stratigraphy to a scale above seismic resolution. This concept provide a greatly improved understanding of facies geometries and reservoir architecture. It has developed into a powerful predictive facies analysis tool for both the hydrocarbon industry and academic research. This new approach has led to the reassessment of areas that in some cases have been the subject of intense geological scrutiny for decades.